Predictors of successful trial with-out catheter following acute urinary retention secondary to benign prostatic hypertrophy - Jha, Aditya A.; Singh, Gagandeep; Govindaiah, Madhu; Solanki, Nimit (International Surgery Journal, 2020)
Background: Acute urinary retention (AUR) is one of the most psychologically distressing complications of benign prostatic hypertrophy (BPH). Attempt of trial without urinary catheter (TWOC) is given to all these patients, failing which they are subjected to surgical management. This study was conducted to analyse the possible predictors of successful trials in such patients. Methods: Patients reporting to our centre with a first episode of spontaneous AUR secondary to BPH were enrolled. Following per-urethral catheterization residual urine volume (RUV) drained, duration of symptoms and international prostate symptom score (IPSS) were recorded. Using trans-abdominal ultrasonography (USG) prostate volume (PV), intra-vesicle prostate protrusion (IPP) and bladder wall thickness (BWT) were measured. Catheter free trial was given after a course of tamsulosin. Success was defined if patients could void >200 ml of urine within six hours of catheter removal with a maximum flow rate of >5 ml/sec and achieved a post void residual (PVR) urine volume of <150 ml. Results: Ninety patients with 58 in successful and 32 in failed group were analysed. Significantly lesser age, IPSS, RUV, IPP and BWT was noted in successful group. Duration of LUTS and PV on USG were statistically insignificant parameters in determining a successful trial. Conclusions: Age, IPSS, RUV, IPP and BWT may have a role in predicting successful TWOC following AUR secondary to BPH.